A preliminary study on foamed bitumen stabilisation for Western Australian pavements - Huan, Yue; Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (Academic Journals, 2010)
Currently, the popularity of conventional cementitious stabilisation had been challenged by an innovative soil improvement technique, known as foamed bitumen stabilisation. Many Australian highway and road agencies have dedicated significant investigation and funds to investigate this technique in order to achieve a more flexible and fatigue resistant stabilised material suitable for a wide range of pavement conditions. This study aimed to report the preliminary study of the foamed bitumen properties and the mix procedures conducted at Curtin University which simulated the construction of the trial foamed bitumen stabilised project in Western Australia. Our findings show that 2.5% of cold water spraying into 180°C virgin Class 170 bitumen can produce foamed bitumen with a 15 to 20 times expansion rate and 20 s half-time suitable for foaming aggregates. Both resilient modulus and permanent deformation tests failed to predict an optimum foamed bitumen content when the aggregate was mixed with 1% hydrated lime, compacted at 100% optimum moisture content and plastic sealed curing for 7 days at room temperature.However, the ratio of crushed granite roadbase to limestone was found to be significant and a mixture consisting of 75% crushed rock base and 25% crushed limestone was determined as the optimum aggregate proportion, as it showed the best performance in unconfined compressive strength tests and obtained relatively higher values in indirect tensile strength tests. Based on our preliminary results, due to adding more foamed bitumen to in-situ recycled aggregate seems to reduce the performance of materials, a more comprehensive laboratory investigation of the foamed bitumen stabilisation process in Western Australia would be essential.